Hypermethylation of HLA-C may be an epigenetic marker in psoriasis. Issue 1 (July 2016) - Chen, Min; Wang, Yan; Yao, Xu; Li, Chengrang; Jiang, Mingjun; Cui, Pangen; Wang, Baoxi
Highlights: The frequency of promoter methylation for HLA-C in the psoriatic epidermis was significantly increased compared with healthy controls. There was no significant difference in HLA-C methylation between psoriatic lesions and non-lesions. The mean HLA-C mRNA expression was significantly higher in psoriatic epidermis than healthy controls, while there is no significant difference between psoriatic lesions and non-lesions. Abstract: Background: There are no published studies that describe the DNA methylation of human leukocyte antigen class I molecules in psoriasis despite the fact that their association to disease has been known for several decades. Objective: we investigated the methylation status of HLA-A, -B and -C loci in psoriatic epidermis. Methods: The DNA and RNA specimens were obtained from the involved and uninvoled epidermis of 56 patients with plaque psoriasis and 28 healthy persons as the control group. Methylation of HLA was examined by MSP and Bisulfite sequencing. HLA-C mRNA expression was examined by Q-PCR. The severity of disease was evaluated by psoriasis area and severity index (PASI). Results: In psoriatic lesions and psoriatic non-lesions, the percentage of promoter methylation for HLA-B was 3.57% (2/56) and 3.57% (2/56), while it was 14.28% (8/56) and 23.21% (13/56) for HLA-C, respectively. Methylation of HLA-A was not be detected in both psoriatic lesions and non-lesions. Methylation of HLA-A, -B and -C loci was not found in healthy controls. The frequency of promoter methylation for HLA-C in the psoriatic epidermis was significantly increased compared with healthy controls (p < 0.05). Interestingly, there was no significant difference in HLA-C methylation between psoriatic lesions and non-lesions (χ 2 = 1.465, p = 0.167), which was further confirmed by using bisulfite sequencing (t = 1.958, p = 0.055). HLA-C methylation was not found in healthy controls. The mean methylation rate of HLA-C in psoriatic lesions is relative to PASI score (r = 0.316, p = 0.018). The mean methylation rate of HLA-C in psoriatic lesions and non-lesions of the patients (onset age ≤18 years) are higher than the other patients, respectively (t = 6.884, p < 0.001; t = 6.551, p < 0.001). The mean HLA-C mRNA expression was significantly higher in psoriatic non-lesions than normal skin (t = 2.895, p = 0.005), while there is no significant difference between psoriatic lesions and non-lesions (t = 1.966, p = 0.054). The mean value of HLA-C mRNA expression is not relative to the promoter methylation of HLA-C in psoriatic lesions and non-lesions, respectively. Conclusions: We first demonstrate hypermethylation of HLA-C gene in psoriatic epidermis, suggesting that HLA-C hypermethylation may be an epigenetic marker in psoriasis.